Evaluasi Sistem dan Prosedur Belanja Tidak Terduga Pada Kantor Dinas Sosial Daerah Provinsi Sulawesi Utara: Evaluasi Sistem dan Prosedur Belanja Tidak Terduga Pada Kantor Dinas Sosial Daerah Provinsi Sulawesi Utara - Lindsay Johannes; Jessy Warongan (Universitas Sam Ratulangi, 2023)
Unexpected Expenditures (BTT) are APBD expenditures in emergencies, urgent needs and returns for overpayments of regional revenues in previous years. The purpose of this study is to evaluate unexpected spending reporting. The research method used is a qualitative approach. Source of data taken from primary data. Data collection procedures using interviews, observation and documentation. The results of this study indicate that the preparation, disbursement, use and accountability of unexpected expenditure funds in 2020 and 2021 are in accordance with the technical guidelines for regional financial management carried out by the Head of the Social Service and the Expenditure Treasurer of the Social Service, which are in accordance with Minister of Home Affairs Regulation No. .77 of 2020 and Regional Head Regulations